Perceived training needs by tutors of family and community medicine and nursing of specialized health training: a qualitative descriptive study - Berlanga-Fernández, Sofía; Rodríguez-Monforte, Miriam; Pérez-Cañaveras, Rosa M.; Valer-Martínez, Alicia; Copetti-Fanlo, Silvia; Simonet-Aineto, Pere J.; Vizcaya-Moreno, Flores; Villafáfila-Ferrero, Rosa (Frontiers in Medicine, 2024)
Introduction Specialized Health Training is a postgraduate training pathway in which physicians and nurses can choose to continue their learning and obtain the qualification of specialist professional in a specific field. The training is eminently practical with different clinical tracks in which nurses and physicians are tutored by clinician tutors. Our research aims to describe the experiences and perceptions of clinician tutors related to their own teaching performance and training needs. Methods We conducted a descriptive qualitative study. The sample consisted of active clinician tutors of specialized health training of family and community nursing and medicine, this being the main inclusion criterion, regardless of the number of years of experience as a tutor. Data were analyzed following a content analysis method. Results Four focus groups were held with 25 participants: 32% nursing tutors (8) and 68% tutors of medicine (17). The main categories identified were: (1) teaching performance; (2) training needs; and (3) characteristics of an ideal training program. The sample consisted of a majority of tutors of medicine compared to nursing. Conclusion Clinician tutors of Specialized Health Training of Family and Community nursing and medicine express the need to acquire pedagogical tools, to develop communication skills and to create a tutor network in order to improve their mentorship practice. Furthermore, more institutional recognition and protected time are also highlighted as important elements for their mentorship role. The findings of our research can serve as a guideline to start designing a training plan that meets the real needs of clinician tutors.